GAMMA SCANNING TECHNIQUE FOR INVESTIGATING DE-ETHANIZER COLUMN: ON FIELD EXPERIMENTAL AT NGL PLANT - Bayu Azmi; Wibisono Wibisono (BATAN, 2019)
GAMMA SCANNING TECHNIQUE FOR INVESTIGATING DE-ETHANIZER COLUMN: ON FIELD EXPERIMENTAL AT NGL PLANT. De-ethanizer column is part of fractionators series at natural gas liquid (NGL) plant. During the production process, there are several common problems happen such as displaced or damaged trays, dry or flooding trays, unequal liquid level on trays, weeping or dumping trays, foaming on trays, etc. Therefore, investigation of column’s internal condition without interupting production process is needed to maintain the production level. Gamma scanning technique has been chosen to investigate 01-C-3401 de-ethanizer column. The column has two segments, the lower (ID: 1900 mm) and the upper (ID: 3200 mm) segments. Total column height (TL to TL) is 36710 mm. The scanning was conducted by positioning collimated gamma source (Co-60, 2.59 GBq) and detector (NaI(Tl)) flanking the column. The collimators move up in parallel by 50 mm and detector counted radiation that penetrated column for 3 seconds every scanning step. The scanning process were performed automatically using winch with AC motor, microcontroller module, computer with LabVIEW as graphical user interface (GUI). The results show mechanical structures of tray #1 - #38 were in good condition. There were no collapsed or flooded trays in the column. The demister was in its position. Chimneys above tray #38 and tray #8 were observed exist. The liquid level during the scanning process were in normal liquid level (NLL) approaching to high liquid level (HLL). Gamma scanning technique has been succesfull to provide the internal structure condition information of the column.